The Wooden Roof Framing Elements, Furniture and Furnishing of the Etruscan Domus of the Dolia of Vetulonia (Southern Tuscany, Italy) - Coradeschi, Ginevra (2022)
The Etruscan Domus of the Dolia remained hidden until 2009, when archaeological excavations began in the Etruscan–Roman district of Vetulonia (Southern Tuscany). Based on the classification of the archaeological materials recovered, the destruction of the Domus and the Etruscan city of Vetulonia was traced back to the 1st century BC. The highly various and precious materials recovered inside the Domus revealed the richness of the building and its inhabitants. With this study, we present the anthracological analyses from the Domus of the Dolia. Wood charcoals were recovered from different house rooms, which had different functions based on the archaeological evidence. The tree species employed for the construction of the roof of the building were deciduous and semi-deciduous oak wood (Quercus sect. robur, Quercus sect. cerris) and silver fir wood (Abies cf. alba). Evergreen oak wood (Quercus sect. suber), boxwood (Buxus sempervirens), beech wood (Fagus cf. sylvatica), maple wood (Acer sp.) and cherry wood (Prunus cf. avium) were adopted for the furniture and furnishings of the house. Moreover, wood charcoal fragments of fruit trees belonging to the family of Rosaceae were identified, documenting a possible garden inside the court of the house. The study shows the use of the local tree species primarily. The silver fir wood and beech wood were likely sourced from the nearby (roughly 60 km) Mount Amiata.